Impact of Intraoperative Dexamethasone on Postoperative Complications and Long-Term Survival in Patients with Non-Small Cell Lung Cancer: A retrospective Propensity Score-Matched Study - Zhu W; Zhu L; Wang X; Tan H (International Journal of General Medicine)
Wenzhi Zhu,1,* Liping Zhu,2,* Xiaoyi Wang,3 Hongyu Tan1 1Key Laboratory of Carcinogenesis and Translational Research (Ministry of Education/Beijing), Department of Anesthesiology, Peking University Cancer Hospital & Institute, Beijing, 100142, People’s Republic of China; 2Department of Hospice Care, Peking University Cancer Hospital (Inner Mongolia Campus), Inner Mongolia, 010010, People’s Republic of China; 3Key Laboratory of Carcinogenesis and Translational Research (Ministry of Education/Beijing), Department of Medical Record Statistics, Peking University Cancer Hospital& Institute, Beijing, 100142, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hongyu Tan, Key Laboratory of Carcinogenesis and Translational Research (Ministry of Education/Beijing), Department of Anesthesiology, Peking University Cancer Hospital & Institute, No. 52 Fucheng Road, Haidian District, Beijing, 100142, People’s Republic of China, Tel +86-13693564036, Email galaxyspark@163.comObjective: This study investigated the impact of intraoperative dexamethasone on postoperative complications and long-term survival in patients with non-small cell lung cancer (NSCLC) undergoing surgery.Methods: Patients with NSCLC who underwent lung resection between January 1, 2006, and December 31, 2009, were included. Patients receiving dexamethasone formed the dexamethasone (DXM) group, while those who did not were assigned to the non-dexamethasone (non-DXM) group. Propensity score matching (PSM) was applied to minimize confounding bias. The primary endpoint was the incidence of postoperative complications.Results: Of the 579 patients included, 224 received intraoperative DXM, while 355 did not. PSM produced a matched cohort of 400 patients (200 in each group). After matching, the DXM group had significantly lower incidences of postoperative pneumonia (P < 0.05), reduced intensive care unit (ICU) ICU occupancy, and shorter postoperative hospital stays (PHS) compared with the non-DXM group (P < 0.05). No significant differences were observed in overall survival (OS) or recurrence-free survival (RFS) between the groups.Conclusion: Intraoperative DXM use reduced the incidence of postoperative pneumonia, ICU occupancy, and PHS. However, no clear association was found between intraoperative DXM use and long-term survival outcomes in NSCLC patients.Keywords: dexamethasone, postoperative complications, survival, NSCLC